Introduction to "Quantum mechanics and reality" - Arroyo, Raoni; Arenhart, Jonas R. B.; de Ronde, Christian; Fernández Mouján, Raimundo (THEORIA. An International Journal for Theory, History and Foundations of Science, 2024)
This paper introduces the Special Issue of Theoria entitled "Quantum Mechanics and Reality". We first comment on its origins related to the VIII International Workshop on Quantum Mechanics and Quantum Information, promoted by the International Network on Foundations of Quantum Mechanics and Quantum Information. We then briefly introduce each contribution individually, bringing the papers together under the Special Issue's topic.